2007
DOI: 10.5194/acpd-7-15911-2007
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Air pollution during the 2003 European heat wave as seen by MOZAIC airliners

Abstract: Abstract. This study presents an analysis of both MOZAIC profiles above Frankfurt and Lagrangian dispersion model simulations for the 2003 European heat wave. The comparison of MOZAIC measurements in summer 2003 with the 11-year MOZAIC climatology reflects strong temperature anomalies (exceeding 4°C) throughout the lower troposphere. Higher positive anomalies of temperature and negative anomalies of both wind speed and relative humidity are found for the period defined here as the heat wave (2–14 August 2003),… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 39 publications
1
27
0
Order By: Relevance
“…A more detailed analysis of the meteorology during the period of analysis can be found in Tressol et al (2008). We will analyse the same periods considered in that work -before (16-31 July 2003), during (2-14 August 2003) and after (16-31 August 2003) the heat wave -in order to test the model's performance under moderate and extreme meteorological conditions.…”
Section: Statistics Used For Model Evaluationmentioning
confidence: 99%
See 4 more Smart Citations
“…A more detailed analysis of the meteorology during the period of analysis can be found in Tressol et al (2008). We will analyse the same periods considered in that work -before (16-31 July 2003), during (2-14 August 2003) and after (16-31 August 2003) the heat wave -in order to test the model's performance under moderate and extreme meteorological conditions.…”
Section: Statistics Used For Model Evaluationmentioning
confidence: 99%
“…The decrease in both O 3 and CO above Frankfurt in the middle of the heat wave as a consequence of the ventilation by a low-pressure system is reproduced by the models. However all model runs have difficulties in reproducing the previous strong increase in CO, which is at least partly associated with the transport from Portuguese fires (Hodzic et al, 2007;Tressol et al, 2008). This was expected since the models use monthly averaged emission data and do not include a parameterisation for injection heights of fire emissions; therefore they cannot account for the strong transport of CO from Portuguese fires to other countries of Western and Central Europe, particularly during 6-10 August, the period for which Tressol et al (2008) found a contribution of biomass burning to CO above Frankfurt of around 35%.…”
Section: Comparison With O 3 and Co Profiles From Mozaicmentioning
confidence: 99%
See 3 more Smart Citations